The socioeconomic dimensions of HIV/AIDS in Africa : challenges, opportunities, and misconceptions - Sahn, David E. (Africa series (Zed Press), 2010)
Since the 1980s HIV/AIDS has occupied a singular position because of the rapidly emergent threat and devastation the disease has caused, particularly in sub-Saharan Africa. New infections continue to create a formidable challenge to households, communities, and health systems: last year alone, 2.7 million new infections occured globally. Sub-Saharan Africa remains the epicenter of the suffering, with around two-thirds of infected individuals worldwide found there, and a disproportionate number of deaths and new infections.